Mining Activities at the Pit 2 Electrification Mine Location at West Banko PT Bukit Asam, Tbk. Tanjung Enim, South Sumatera - Monica Fadhillah Afrina Wati; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2024)
PT Bukit Asam (Persero) Tbk is a State-Owned Enterprise (BUMN) which was founded on March 2 1981 located in Tanjung Enim, South Sumatera. The purpose of production activities is to produce minerals that have a price or selling value. In coal production activities there are two productions that can be carried out, namely coal production and overburden production. PT Bukit Asam Tbk. implementing open-pit mining methods. The mining method in Pit 2 Banko Barat uses the strip mining method, because this method is used in coal deposits with a relatively small slope (dip), the slope (dip) in Pit 2 Banko Barat is N200OE/25O. Mining activities in Pit 2 Banko Barat are still being carried out are mining (exploitation), processing, marketing and post-mining activities. In coal mining activities, PT Bukit Asam Tbk. using a shovel PC 3000 earth digging tool and a Belaz transportation tool. Apart from loading and unloading excavation equipment as the main mining equipment, there is also supporting equipment such as motor graders, bulldozers, water tanks and fuel tanks to obtain optimal and maximum production results. In coal mining activities in the West Banko Mine area, PT Bukit Asam Tbk. using a Shovel PC 3000 for overburden activities, while the transportation equipment is a DT Nissan CWB 45 for coal mining activities and the HD rigid truck Belaz 75135 for overburden activities